PENGARUH PENGELUARAN PEMERINTAH PROVINSI DI INDONESIA UNTUK FUNGSI EKONOMI, KESEHATAN, PENDIDIKAN SERTA PERUMAHAN DAN FASILITAS UMUM TERHADAP PENDUDUK MISKIN TAHUN 2011-2013 - Azwardi Azwardi (Jurnal Ekonomi Pembangunan, 2014)
This research was aimed to know the influence of economics expenditure, health expenditure, education expenditure and housing and public facilities expenditure on poverty in Indonesian’s provinces. The methode of analysis that used in this research is pooling regression. This research used panel data which collected from Statistics Indonesia Finance Ministry from 2011 until 2013 include 33 provinces in Indonesia. The research result showed that the variables that had positive influence are economics expenditure and health expenditure. Meanwhile, the variables that had negative influences are education expenditure and housing and public facilities expenditure. Keywords: Province’s Expenditure, economy, health, education, housing and public facilities, poverty.